2022
DOI: 10.31620/jccc.06.22/11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Firm Created, and User Generated Social Media Communications on Consumer-Brand Metrics of Smartphones During Covid-19

Abstract: This study employs the S-O-R approach to analyze the impact social media communications experts on consumer-brand metrics of smartphones during COVID-19. A survey of 513 millennials from India through a well-structured questionnaire reveal that user-generated content on social media positively influences the purchase intent of consumers whereas firm-created social media content does ‟t directly influence the purchase intention. In addition to it, social media content generated by the firm significantly and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
1
0
2
Order By: Relevance
“…H4: UGSMS has a positive effect on brand passion Article's contents are provided on a Attribution-Non Commercial 4.0 Creative commons license. To see the complete license contents, please visit http://creativecommons.org/licenses/by-nc/4.0/ According to Singh & Kumar (2022), social media engagement results in three types of activities, namely consuming content, creating content, and contributing to the content. A study examining the impact of user-generated content reported that negative reviews could damage the success of video games.…”
Section: Firm-created Social Media Communication (Fcsmc)mentioning
confidence: 99%
“…H4: UGSMS has a positive effect on brand passion Article's contents are provided on a Attribution-Non Commercial 4.0 Creative commons license. To see the complete license contents, please visit http://creativecommons.org/licenses/by-nc/4.0/ According to Singh & Kumar (2022), social media engagement results in three types of activities, namely consuming content, creating content, and contributing to the content. A study examining the impact of user-generated content reported that negative reviews could damage the success of video games.…”
Section: Firm-created Social Media Communication (Fcsmc)mentioning
confidence: 99%
“…Penelitian dilakukan di Jakarta pada bulan Juni tahun 2022 dengan mengumpulkan data melalui kuesioner online pada platform google forms [12]. Jumlah sampel minimal adalah 5 kali dari total jumlah item pernyataan yang digunakan pada kuesioner [13]. Terdapat 17 indikator pernyataan dalam penelitian ini, sehingga minimal jumlah sampel adalah : 5 x 17 = 85.…”
Section: Metode Penelitianunclassified
“…Pengujian instrumen dalam penelitian dilakukan dengan menguji validitas dan realibilitas. Uji validitas digunakan untuk mengukur apa yang seharusnya diukur, sedangkan uji reliabilitas digunakan untuk penetapan konsitensi, akurasi dan prediktibilitas suatu alat ukur [13].…”
Section: Metode Penelitianunclassified